UPAYA PEMERINTAH INDONESIA DALAM MENGHADAPI PROBLEMATIKA TKI DI ARAB SAUDI - Wike Rulita Harik (HI 16 UMY 014, 2016)
*14 Indonesia is a developing countries that still has many issues such as unemployment problems. Indonesian citizens choose to work as migrant workers in some countries. One of the main countries that demand is Saudi Arabia. However, many Indonesian Workers are exposed cases in the State of Saudi Arabia, such as sexual harassment, death penalty, unpaid salaries, maltreatment and others. Indonesia as a country who sent many migrant workers to Saudi Arabia should protect Indonesian Workers. Indonesian government took some policies to reduce the number of cases happened to migrant workers in Saudi Arabia such as the implementation of the moratorium workers to Saudi Arabia by the Indonesian government which has positive and negative effect.